Analisis Pengaruh Hasil Investasi Terhadap Laba Perusahaan Asuransi Jiwa Syariah di Indonesia - Tab, Hendra (Journal Research of Economic and Bussiness, 2023)
This study aims to determine the effect of investment returns on profits of Islamic life insurance companies in Indonesia. This study consists of the investment return variable as the independent variable and company profit as the dependent variable. The data analyzed are the company's annual financial statements for the period 2017 to 2022. The results showed that investment returns show a value at an alpha coefficient of 5% (t-stat = 2.498 > 1.667) and prob. 0.015 <0.05. So based on the research results show that the hypothesis is accepted, namely investment results have a significant effect on net income at PT. Sharia Life Insurance Period 2017-2022.